Efectos de la inversión extranjera directa de Colombia y México al sector agrícola (2023)
The present monograph analyzes Foreign Direct Investment (FDI) in the agricultural sector of Colombia. FDI has the potential to drive economic development and generate benefits such as employment, foreign exchange, competition, and technology transfer. Colombia stands out for its agro-industrial sector and attracts foreign investment due to its fertile land and natural resources. Additionally, a comparison is made with Mexico, as it is one of the Latin American countries with the highest FDI inflows. This comparison is carried out using two analysis tools (PESTEL and SWOT). It is inferred that although Colombia surpasses Mexico in agricultural investment, both countries face challenges and need to implement effective policies, improve education and training, promote innovation, and diversify agricultural production to attract investments and enhance competitiveness.